Evaluation of circulating tumor DNA by electropherogram analysis and methylome profiling in high-risk neuroblastomas - Trinidad, Eva María; Juan-Ribelles, Antonio; Pisano, Giulia; Castel, Victoria; Cañete, Adela; Gut, Marta; Heath, Simon; Font de Mora, Jaime (Frontiers in Oncology, 2023)
ABSTRACT Liquid biopsy has emerged as a promising non-invasive diagnostic approach in oncology because the analysis of circulating tumor DNA (ctDNA) reflects the precise status of the disease at diagnosis, progression and response to treatment. However, the limited blood sample size which can be obtained from children with cancer and the ctDNA content occasionally diluted by non-tumor cell-free DNA (cfDNA) complicate optimal quantities of material for high-throughput sequencing studies. Numerous efforts are ongoing to better develop liquid biopsy assays as minimally invasive tools for diagnostic, prognostic, and disease monitoring needs in childhood cancer care. We addressed these problems by assessing whole genome methylsequencing in high-risk neuroblastoma patients. Neuroblastoma is an extracranial solid tumor most common in children and responsible for up to 15% of cancer-related deaths. This high death rate has prompted the scientific community to search for new therapeutic targets to improve treatment and quality of life for young patients. In the search for new biomarkers and druggable targets, DNA methylation offers a new hopeful source of these molecules. The abnormal distribution of DNA methylation is one of the hallmarks of many cancers and has a huge potential in neuroblastoma. DNA methylation analysis could perform from ctDNA, being an extremely useful and minimally invasive tool; however, this approach presents several issues yet. In this article, we present an improved method for methylome studies of blood-derived plasma ctDNA from high-risk neuroblastoma patients. Based on our data, we also assess several bioinformatic approaches for analyzing DNA methylation sequencing data and we further implement them to identify from electropherogram profiles the suitable ctDNA-containing samples for methylome studies. Although we focused on DNA methylation and copy number variations, the same pipeline could also be used for single nucleotide variants, but not for chromosomal rearrangements. Our results refine the use of electropherogram profiles to adequately select optimal samples for subsequent high-throughput analysis and support the use of liquid biopsy followed by enzymatic conversion of unmethylated cysteines to assess the methylomes of neuroblastoma patients.